2015
DOI: 10.1101/gr.184325.114
|View full text |Cite
|
Sign up to set email alerts
|

The clustering of functionally related genes contributes to CNV-mediated disease

Abstract: Clusters of functionally related genes can be disrupted by a single copy number variant (CNV). We demonstrate that the simultaneous disruption of multiple functionally related genes is a frequent and significant characteristic of de novo CNVs in patients with developmental disorders (P = 1 × 10−3). Using three different functional networks, we identified unexpectedly large numbers of functionally related genes within de novo CNVs from two large independent cohorts of individuals with developmental disorders. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 69 publications
(122 reference statements)
3
26
0
1
Order By: Relevance
“…In addition to HOX genes, we found that developmental genes were also clustered in the genome regardless of gene family, which led to the identification of 31 genomic loci containing at least four predicted developmental genes each. Our finding is consistent with a recent study showing the clustering of functionally related genes in the genome (Andrews et al., ). Since CNVs detected in products of conception could affect multiple clusters of developmental genes, which eventually led to the pregnancy loss or severe congenital malformations, we further examined the clinical phenotypes caused by CNVs affecting each genomic loci with clustered developmental genes.…”
Section: Discussionsupporting
confidence: 94%
“…In addition to HOX genes, we found that developmental genes were also clustered in the genome regardless of gene family, which led to the identification of 31 genomic loci containing at least four predicted developmental genes each. Our finding is consistent with a recent study showing the clustering of functionally related genes in the genome (Andrews et al., ). Since CNVs detected in products of conception could affect multiple clusters of developmental genes, which eventually led to the pregnancy loss or severe congenital malformations, we further examined the clinical phenotypes caused by CNVs affecting each genomic loci with clustered developmental genes.…”
Section: Discussionsupporting
confidence: 94%
“…Compared with single-nucleotide variants (SNVs), CNVs are responsible for more than ten times the heritable sequence differences in general populations (Pang et al 2010), and their genome-wide map has been comprehensively studied (Zarrei et al 2015). Likewise, they are involved in the pathogenesis of both sporadic Mendelian disorders and complex multifactorial disease (Andrews et al 2015; Stankiewicz and Lupski 2010; Weischenfeldt et al 2013). It is noteworthy that common CNVs and SNPs in relatively nearby regions have been associated with an increased likelihood of causing the same phenotype, such as Crohn disease (McCarroll et al 2008a), rheumatoid arthritis and type 1 diabetes etc.…”
Section: Introductionmentioning
confidence: 99%
“…Adding exome genes to the network of each sibling showed that, as stated by Andrews et al [30], the more connected the genes were, the more severe was the clinical presentation. The male sibling had a network that was more well connected, and, with the inclusion of the exome, more genes from the translocation were included.…”
Section: Discussionmentioning
confidence: 95%
“…However, recurrent CNVs have been associated with an increased risk of other neurodevelopmental disorders, such as schizophrenia and epilepsy [28]. Various authors have attempted to improve the understanding of the nature of CNVs and to elucidate their contribution to specific phenotypes [29,30]. In patients with developmental disorders, Andrews et al [30] found that, if protein-protein interactions are taken into account, patients with genic (especially de novo ) CNVs, disrupting the same cluster of functionally related genes, present phenotypes that are more similar than would be expected.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation